Government Governance, Government Quality, Transportation Infrastructure, and the Economic Growth: Evidence from Indonesia - Zainal, Andri; Farza, Tengku Citra Nisa; Putra, Pasca Dwi; Harahap, Khairunnisa; Welly, Yerisma (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study aims to provide a descriptive analysis of the relationship between government administration, quality of government, transportation infrastructure, and economic growth in Indonesia during the period 2001 to 2018. The results of the analysis show that road length has a positive relationship with economic growth, while the amount of loading and unloading of goods domestic and foreign shipping has a negative relationship with economic growth. Government quality (as stated by Unqualified Opinion on the financial reports of the Ministry of Communications and the Ministry of Public Works and Public Housing provided by the Supervisory Board of the Republic of Indonesia) shows good quality results over the last three years.